THE ROLE OF RECOMBINANT IL-10 ON THE SERUM LEVEL OF TNF-?, ONE HOUR POST TRAUMATIC BRAIN INJURY OF THE WISTAR RAT - Adhimarta, Willy; Islam, Andi Asadul; Maliawan, Sri; Lowrence, Gatot S.; Patellongi, Ilhamjaya (BALI MEDICAL JOURNAL, 2015)
Background: Brain injury often occurs not only primary brain injury, but often also occur secondary brain injury. Inflammation is a process that occurs immediately after trauma characterized by activation of the mediator substance. TNF-? is a major cytokinee involved in the inflammatory processes that have adverse effects if the serum level are excessive. There needs to be a balance of the inflammatory process in the brain injury so things that harm does not occur. As anti-inflammatory IL- 10 plays an important role in maintaining the balance. The objective of this study is to determine the effect of IL-10 intervention as an anti -inflammatory will decrease the serum level of TNF-? in traumatic brain injury. Material And Method: Experimental Study in the Rattus Wistar rats, post test control group design, male, aged 3-4 months, with body weight (BW) 300-400g, were obtained from the Laboratory Animal Faculty of Medicine, University of Hasanuddin as much as 24 tails, which is the result of breeding. Subjects were divided into four groups, each group of six rats, treated with controlled cortical impact model (Feeney’s weight-drop) of traumatic brain injury. Blood taken with capillary tube in retro-orbita plexus or sinus.This study has approved by ethical clearance for research. Results: Levels of TNF-? group of rats 1 hour post-trauma without administration of recombinant IL-10 (28.58 ± 7.28) pg / mL; was significantly higher (p